Free non-specific relative sentences under the perspective of discursive-functional grammar - Amorim, Camila Rodrigues de [UNESP]; Garcia, Talita Storti [UNESP] (Revista Virtual Estudos Linguagem, 2022)
This article investigates sentences headed by the indefinite relatives cualquiera, quienquiera, comoquiera and dondequiera. According to the Nueva Gramatica de la Lengua Espanola (2010), the structure of these constructions is closer to that of a free relative, since they lack a syntactically expressed nucleus or antecedent. In order to analyze the pragmatic, semantic and morphosyntactic properties of these sentences, we adopt Hengeveld and Mackenzie's (2008) Functional Discourse Grammar, which allows us to identify a series of non-lexical nuclei, both at the Interpersonal Level and at the Representational Level. For the selection and analysis of the data, the CREA corpus (Corpus de Referencia del Espanol Actual) was chosen. In general, the results show that, in the absence of an explicit nominal head, the referential term of the embedded predication is not filled with lexical material and a concrete and referential entity is characterized as a state of affairs.
Keywords: Spanish; indefinite relatives; free relative clauses; Functional Discourse Grammar